The Role of Perceived Stress in Marital Boredom Due to Ego_Strength and Mindfulness - Sheida Alipour; Leila Heydarinasab (روانشناسی بالینی و شخصیت)
Introduction: Boredom is defined as a state of mental, emotional, and physical exhaustion resulting from prolonged exposure to emotionally draining conditions. Investigating and identifying the factors that contribute to marital boredom, as well as implementing strategies to prevent it, can significantly strengthen the family unit and sustain the marital relationship. The present study aims to explore the mediating roles of "ego-strength" and mindfulness in the relationship between perceived stress and marital boredom.Method: The present study employs a correlational and structural equation modeling approach, utilizing Amos 23 and SPSS 23 software for data analysis. The statistical population of the study comprises all married female employees from Shahed University, Iran Medical Sciences University, and Shahid Beheshti University in Tehran. A sample of 369 individuals was selected using a purposive sampling method. The instruments utilized in this study include the Paiz Marital Burnout Questionnaire, Cohen's Perceived Stress Scale, Maxstrom et al.'s Self-Strength Scale, and the Five-Factor Mindfulness Questionnaire.Results: The results of the study indicated a meaningful positive relationship between marital boredom and perceived stress. The relationship between marital boredom and both ego-strengh and mindfulness is negative and inversely significant. The relationship between perceived stress and both ego-strengh and mindfulness is negative and inversely significant. Additionally, the findings indicate that perceived stress, mediated by self-strength and mindfulness, can meaningfully explain marital boredom through structural relationships. Discussion and conclusion: Based on the findings of this study, it can be concluded that the perceived tensions and stresses in the lives of married women, due to their self-strength and mindfulness, can significantly predict their marital burnout in relation to their husbands.